High noise immunity phase generated carrier demodulation technology for the modulation depth influence elimination. (October 2022) - Sun, Kang; He, Mengyang; Han, Yu; Zhao, Laijun; Dong, Shuchun
Abstract: In the traditional phase generated carrier (PGC) demodulation algorithms, the modulation depth is an important factor affecting the demodulation effect, and the demodulated signal can be distorted with the modulation depth variation. To address this limitation, this study proposes a method that introduces the differential self-division operation in the traditional PGC-Arctan algorithm framework to eliminate the influence of the modulation depth of distributed optical fiber acoustic sensor system. The simulation results of signal demodulation at different modulation depths and different SNR values show that the proposed algorithm can eliminate adverse effects of the modulation depth and achieve good demodulation performance. An experimental platform is built to verify the simulation results further. Experimental results show that under different modulation depths, the amplitude error of the proposed algorithm is 0.105%, and the total harmonic distortion is 0.068%. Furthermore, the dynamic range of the proposed algorithm is up to 62.5 dB. The comprehensive analysis results verify that the proposed algorithm can effectively eliminate the modulation depth influence, indicating its good stability and noise resistance. Therefore, the proposed algorithm has a good application prospect in high-performance optical fiber acoustic sensing systems. Highlights: A novel differential self-division operation is brought into the PGC-Arctan algorithm framework. The influence of the modulation depth of the two-channel mixing signal can be eliminated. It achieves higher stability and lower harmonic distortion than the PGC-Arctan algorithm.